A cross-sectional study of the prevalence and factors associated with symptoms of perinatal depression and anxiety in Rwanda - Marie Providence Umuziga; Oluyinka Adejumo; Michaela Hynie (BMC, 2020)
Abstract Background Perinatal depression and anxiety are increasingly recognized as important public health issues in low and middle-income countries such as Rwanda and may have negative consequences for both mothers and their infants. Maternal mental health may be particularly challenged in Rwanda because of the prevalence of risk factors such as poverty, low education levels, negative life events and marital problems. However, there are limited data about perinatal depression and anxiety symptoms in Rwanda. This study thus aimed to explore the prevalence of symptoms of perinatal depression and anxiety in Rwanda, and factors associated with them. Methods A sample of 165 women in the perinatal period (second and third trimester of pregnancy, up to 1 year postnatal) were interviewed individually over 1 month in October 2013. Women were interviewed at 5 of 14 health centres in the Eastern Province or the affiliated district hospital. Participants answered socio-demographic questions and scales measuring symptoms of perinatal depression (EPDS: Edinburgh Postnatal Depression Scale) and anxiety (SAS: Zung Self-rating Anxiety Scale). Results Among women in the antenatal period (N = 85), 37.6% had symptoms indicating possible depression (EPDS ≥10) and 28.2% had symptoms associated with clinical levels of anxiety (SAS > 45). Among women within the postnatal period (N = 77), 63.6% had symptoms of possible depression, whereas 48,1% had symptoms of probable anxiety. Logistic regression showed that symptoms of postnatal depression were higher for respondents who had four or more living children relative to those having their first child (Odds Ratio: 0.07, C.I. = 0.01-0.42), and for those with a poor relationship with their partner (Odds Ratio: .09, C.I. =0.03-0.25). Any lifetime exposure to stressful events was the only predictor of symptoms of postnatal anxiety (Odds Ratio = 0.20, C.I. = 0.09-0.44). Conclusions Symptoms of postnatal depression and anxiety were prevalent in this Rwandan sample and most strongly predicted by interpersonal and social factors, suggesting that social interventions may be a successful strategy to protect against maternal mental health problems in the Rwandan context.